A Novel PROMSIS Vertical Handoff Decision Algorithm for Heterogeneous Wireless Networks - Shengmei Liu; Zhongjiu Zheng; Su Pan (International Journal of Distributed Sensor Networks, 2013)
A novel preference ranking organization method by similarity to ideal solution (PROMSIS) vertical handoff algorithm is proposed for heterogeneous wireless networks, and its essential idea includes the preference structure of the PROMETHEE and the concept of Euclid distance of the TOPSIS. Four 3GPP defined traffic classes are considered in performance evaluation. An attribute matrix is constructed considering some major attributes. Handoff decision meeting multiattribute QoS requirement is made according to the traffic features. The weight relation of decision elements is determined with the least square (LS) approach. The final decision is made using the proposed PROMSIS algorithm based on the attribute matrix and weight vector. The simulation results have manifested that the proposed PROMSIS algorithm can provide satisfactory vertical handoff performance, and the LS-PROMSIS algorithm can be fit to the characteristics of the traffic.